Oilfield Produced Water Management: Treatment, Reuse and Disposal - Baghdad Science Journal (مجلة بغداد للعلوم)
Produced water is accompanied with the production of oil and gas especially at the fields producing by water drive or water injection. The quantity of these waters is expected to be more complicated problem with an increasing in water cut which is expected to be 3-8 barrels water/produced barrel oil.Produced water may contain many constituents based on what is present in the subsurface at a particular location. Produced water contains dissolved solids and hydrocarbons (dissolved and suspended) and oxygen depletion. The most common dissolved solid is salt with concentrations range between a few parts per thousand to hundreds parts per thousand. In addition to salt, many produced waters also contain high levels of heavy metals like zinc, barium, chromium, lead, nickel, uranium, vanadium and low levels of naturally occurring radioactive materials (NORM).This study will highlight the main aspects of the different international experiences with the produced water treatment for subsequent reuse or disposal. These different treatment methods vary considerably in effectiveness, cost and their environmental impacts. Samples of produced water from Al-Mishrif formation in ten wells belongs to five fields southern Iraq were taken and analyzed chemically to define the basic features of these waters and to have guide lines for the best strategy that required handling the increased water cut in these fields.